Wittgenstein and Psychoanalysis: A Critique of the Signifying Reason: Is Wittgenstein’s a Perspicuous Representation - Sergio Benvenuto (EJP import test, 2014)
Summary: The author analyzes the philosophical relationships between Wittgenstein and Freud, trying to explain the reasons for the apparent ambivalence of the former towards the latter. In fact, Wittgenstein seems to be at once an admirer of Freud (he considered practising psychoanalysis himself as a psychiatrist) and a bitter critic of his scientific claims. The author explains these contradictions with Wittgenstein’s complex, essentially negative, attitude towards modern science. Hence his criticism of Freud as too much of a “scientist” on the one hand, and his appreciation of Freud’s endeavor to “unbind mental knots” on the other, a strength that he considered akin to his own philosophical project as illustrated in the Philosophische Untersuchungen. In fact, both Wittgenstein’s philosophy and psychoanalysis contain something the author calls a Critique of the Signifying Reason.
Keywords: Cantor& #x27; s Proof; Goethian Science; Linguistic Games; the Real; Wittgenstein & amp; Freud